Policy Analysis of Regional Regulation No. 14 of 2011 Concerning Semarang City Regional Spatial Planning for Flood Management: A Qualitative Study - Naftali, Fadillah Zulfa; Chika Fatika Sari; Rayi Rajib Kusuma (HM Publisher, 2024)
Semarang City, as one of the metropolitan cities in Indonesia, is often hit by floods. This is caused by various factors, including regional spatial planning that is not well planned. Regional Regulation (Perda) No. 14 of 2011 concerning Semarang City Regional Spatial Planning (RTRW) is expected to be a solution to overcoming flooding problems. This research aims to analyze the effectiveness of Regional Regulation No. 14 of 2011 in dealing with floods in Semarang City. This research uses qualitative methods with data collection techniques through interviews, observation and documentation studies. The data obtained was analyzed using qualitative data analysis techniques. The research results show that Regional Regulation No. 14 of 2011 has several weaknesses in dealing with floods in Semarang City. These weaknesses include: Lack of community involvement in the preparation of the RTRW: The community was not actively involved in the process of preparing the RTRW, so that their aspirations were not properly accommodated. Lack of synchronization between RTRW and other policies: RTRW is not synchronized with other policies related to flood management, such as coastal area spatial planning policies and drainage policies. Lack of law enforcement: Law enforcement regarding RTRW violations is still weak, resulting in many land conversions occurring which exacerbate flooding problems. In conclusion, Regional Regulation No. 14 of 2011 concerning Semarang City RTRW has several weaknesses in dealing with floods. These weaknesses make this policy ineffective in achieving its goals. To increase the effectiveness of this policy, several steps need to be taken, such as increasing community involvement, increasing synchronization between policies, and increasing law enforcement.